Artisanal miners of Pataz, a formalization experience - Trelles, Martin (2021)
Artisanal mining is an activity that can have a high economic impact and subsistence for artisanal miners. When colliding with the formal order, it is prone to disagreement between its social actors, represented by the triad: State, Mining Company and artisanal miners. This research work addresses the conflict between Compañía Minera Poderosa and the artisanal miners of Pataz, after the events that occurred in 2013. The hypothesis of the work is that the Commercialization Protocol and the benefits of the formalization achieved the solution of the conflict between Minera Poderosa and the artisanal miners Ama Pataz. Being an ex post facto study, we reconstruct the case with various sources: informative, personal communications and interviews with social actors. A Survey was carried out on 70 formalized miners in the concession area in order to measure their perceptions of formalization. In the end, the favorable perception of the benefits of the formalization promoted by Minera Poderosa is demonstrated.